Curriculum as Political Hostage: A Genealogy of 'Ganti Menteri Ganti Kurikulum' as Systemic Trauma in Indonesian Education - Rian Sigit Gesang Permana; Mahmud Sahroni; Basirun Basirun; Ari Fatihatul Hidayah (Indonesian Journal of Education and Youth Development, 2025)
This study investigates the persistent phenomenon of Ganti Menteri, Ganti Kurikulum (Change Minister, Change Curriculum) in Indonesian education, analyzing it not merely as administrative inconsistency but as a structural pathology where curriculum policy functions as a tool for political legitimacy. Utilizing a qualitative library research method underpinned by Michel Foucault’s genealogical analysis and institutional trauma theory, this research traces the trajectory of curriculum reforms from the Old Order (1947) to the current Kurikulum Merdeka. The findings reveal that curriculum changes are frequently driven by legitimacy through negation a political logic where new ministers validate their authority by pathologizing predecessor policies and sustained by a proyek economy that incentivizes frequent material procurement. This cycle of discontinuity inflicts systemic trauma on the educational ecosystem, manifested as chronic teacher reform fatigue, the erasure of institutional memory, and administrative paralysis. The study concludes that unless curriculum development is decoupled from the five-year political cycle through a legally binding Grand Design and an independent oversight commission, Indonesian education will remain trapped in a state of perpetual, superficial reinvention.